The Eﬀect of Pesticide Application on QTLs Controlling Traits in Barley - Bakhtiari, Samira; Sabouri, Hossein; Mollashahi, Mehdi; Moghaddam, Hossein Hosseini (Acta Biologica Szegediensis, 2020)
Among cereals, barley (Hordeum vulgare L.) ranks fourth in consumption worldwide. Among barley breeding goals, one can refer to gene mapping, studying their inheritance, and saturated genetic linkage maps. Problems with pesticide applications include reduced genetic diversity, reduced nitrogen fixation, and destruction of the habitat of especially endangered species. The effect of pesticide application on the emergence of QTLs expressing traits in experimental barley was investigated using 104 barley F2:4 families from Badia × Kavir cross. A total of 25 QTLs were mapped for all traits. In non-using pesticides, 12 QTLs were identified for peduncle length, stem diameter, flag leaf length, and awn length. It was found that qFL-4 has major effects on flag leaf length. or using the pesticide, 13 QTLs were detected that QTLs related to stem diameter, grain weight, flag leaf length explained a high percentage of phenotypic variation. The results of this study showed that pesticide application affects the expression of some genes in barley. Besides, major-effect trait-controller QTLs and their associated markers can be used in marker-assisted selection (MAS) programs.